SUMOylation machinery protein, PIAS4 role in breast cancer cell proliferation and drug sensitivity - Mohammed A. M. Salih; Mohamed M. A. E. L. Salem; Muhammad Ali Shahid; Hussein A. S. Elrewey; Ritchie Williamson; Sriharsha Kantamneni (Molecular Biology Reports, 2026)
Purpose Breast cancer is a significant global health issue, with resistance to doxorubicin (DOX) posing a major challenge to effective treatment. SUMOylation, a post-translational modification process, is linked to cancer progression and therapy resistance. PIAS4, a SUMO E3 ligase involved in maintaining genome stability and stress response, may play a role in these mechanisms. However, its function in breast cancer progression and DOX resistance remains uncertain. This study investigates the potential role of PIAS4 in mediating DOX resistance in breast cancer. Methods and results Naked mole-rats (NMRs) are cancer-resistant rodents with improved genome maintenance, yet the role of SUMOylation in this trait remains unclear. SUMOylation machinery gene expression levels are investigated using qPCR in NMR tissue in comparison with carcinogenic breast cancer (MCF-7) cell line. Functional studies are performed in MCF-7 cells overexpressing PIAS4 to demonstrate effects on proliferation, invasion, drug sensitivity, and protein expression in the presence and absence of DOX treatment. While most SUMOylation genes were expressed at low levels in NMR intestinal tissues, PIAS4 showed higher expression compared to MCF-7 cells. PIAS4 overexpression in MCF-7 cells significantly decreases colony formation, invasiveness, and resistance to DOX. Western blot analysis showed downregulated Bcl-2 protein levels after DOX treatment, indicating a potential role in apoptosis evasion. Conclusion PIAS4 expression level plays a role in breast cancer cell survival, invasiveness, and chemoresistance, partly by altering anti-apoptotic pathways. These findings position PIAS4 as a potential biomarker and therapeutic target for overcoming resistance to anthracycline-based therapies in breast cancer.

Immunoinformatics-guided design of a multi-epitope vaccine targeting the envelopment polyprotein of oropouche virus - Muhammad Naveed; Aroosa Athar; Afifa Tariq; Muhammad Asim; Muhammad Nouman Majeed; Rania Ali El Hadi Mohamed; Manal F. Elkhadragy; Maher S. Alwethaynani; Mai M. Almsaud; Ghulam Nabi (Molecular Genetics and Genomics, 2026)

Scalable core-sheath braided yarn-based textile triboelectric nanogenerator for energy harvesting and human motion sensing - Satyaranjan Bairagi; Muhammad Zada; Daniel M. Mulvihill; S. Wazed Ali; Carlo Menon (Chemical Engineering Journal, 2026)

Engineering of novel N-TiO2/P-doped graphene oxide nanocomposite: Mechanistic insights into the photocatalytic removal of benzophenone-3 and H2 production - Wisal Ahmad; Suyeon Jeon; Roman Shah; Dilaram Khan; Syed Izaz Ali Shah; Muhammad Anwar; Raed Al-Juboori; Asad Ali; Noor S. Shah; Javed Ali Khan; Changseok Han (Chemical Engineering Journal, 2026)

Molecular mechanisms and integrated breeding strategies for durable resistance to rice blast and other major pathogens - Daud Ali Shah; Muhammad Usama Younas; Zameer Hussain Jamali; Usman Zulfiqar; Mohammed S. Alotaibi; Mayank Anand Gururani; Owais Iqbal (Physiological and Molecular Plant Pathology, 2026)

Influence of Temperature and Hydrogen Peroxide Treatment on the Physiochemical and Adsorptive Characteristics of Rice Stalk Biochar for Cadmium Remediation: A Sustainable Solution - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Awais Ahmad; Waed Alahmad; Mohammed S. Alotaibi; Saqer S. Alotaibi; Sajad Ali; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Proteome conserved multi-epitope-based vaccine construct against Nipah virus - Taimoor Khan; Tayyab Ali; Muhammad Suhaib Qudus; Gadallah Mohamed; Farukh S. Sharopov; Adam Junka; Yanfang Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Pharmacokinetic evaluation and in vivo anti-inflammatory potential of cyanoacetate derivatives of succinimide - Aini Pervaiz; Muhammad Saeed Jan; Ali Khan; Bushra Ansari; Imad Ahmad; Wadood Ali Shah; Syed Muhammad Mukarram Shah; Abdur Rauf; Abdullah S. M. Aljohani; Waleed Al Abdulmonem; Marcello Iriti (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
The purpose of the study is to evalute the in vivo anti -inflammatory activity of newly synthesized cyanoacetate derivatives of succinimides (C-23, C-31, and C-44) and to elucidate their possible mechanisms of action through key inflammatory mediator pathways. Anti-inflammatory activity was assessed using carrageenan-induced paw oedema and arachidonic acid-induced ear oedema models in vivo. Mechanistic involvement was investigated through histamine-, prostaglandin-, leukotriene-, and bradykinin-induced paw oedema assays. In silico ADME studies were performed to predict pharmacokinetic properties and metabolic interactions. All tested compounds exhibited significant anti-inflammatory activity, with C-44 showing the highest potency. Mechanistic studies indicated that the anti-inflammatory effects were predominantly mediated via inhibition of prostaglandin and leukotriene pathways. ADME predictions suggested high gastrointestinal absorption, favourable oral bioavailability, and minimal interaction with major metabolic enzymes. The synthesized cyanoacetate derivatives, particularly C-44, demonstrate promising anti-inflammatory potential with favourable pharmacokinetic profiles, supporting their candidacy for further development as effective anti-inflammatory agents.

Soil Applied Tartaric Acid Mitigates Lead-Induced Toxicity in Chickpea By Modulating Morphophysiological, Biochemical and Genetic Responses - Farwa Tariq; Muhammad Javed; Muhammad Yaqoob; Habib Ali; Muhammad Khubaib Ijaz; Muydin M. Muminov; Muhayyo O. Buranova; Hossam S. El-Beltagi; Sadam Hussain (Journal of Soil Science and Plant Nutrition, 2026)

Photocatalytic CO2 reduction: Fundamental principles, mechanistic pathways and material-specific kinetic insights - Syed Izaz Ali Shah; Muhammad Anwar; Wisal Ahmad; Muhammad Ateeq; Amir Zada; Noor S. Shah; Javed Ali Khan; Changseok Han (Chemical Engineering Journal, 2026)

Development and Optimization of a Fixed Dose Combination Tablet Containing Ibuprofen and Loratadine Using Design Expert and Box-Behnken Design - Muhammad Faheem; Lateef Ahmad; Umar Farooq; Kiramat Ali Shah; Ismail Khan; Abdur Rauf; Omar S. Bahattab; Yahya S. Al-Awthan; Anees Ahmed Khalil; Huda Ateeq (Journal of Pharmaceutical Innovation, 2026)

Attenuating the Dual Injury of Deficit Irrigation and Salinity On Wheat Physiology and Productivity Via Amending Soil with Compost and Biochar - Ahmed R. Abd El-Tawwab; Khaled M. A. Ramadan; Basma R. Abdel-Moatamed; Shimaa A. Abd El-Mageed; Sallah A. Al Hashedi; Zafar Iqbal; Salim A. Ali; Muhammad Munir; Hani S. Saudy; Taia A. Abd El-Mageed (Journal of Crop Health, 2026)

Integrative 16S rRNA characterization, pan-genome, and immunoinformatics approaches for the design of a multi-epitope vaccine against Bacillus cereus, a foodborne pathogen - Muhammad Asim; Muhammad Naveed; Tariq Aziz; Muhammad Toheed; Hafiz Muzzammel Rehman; Nawal Al-Hoshani; Rania Ali El Hadi Mohamed; Maher S. Alwethaynani; Areej A Alhhazmi; Manal F. Elkhadragy (World Journal of Microbiology and Biotechnology, 2026)

Balancing Nutrient Enrichment and Heavy Metal Stress: Impacts of Wastewater Irrigation on Aromatic Crops - Rabia Bibi; Mehmooda Munazir; Amina Kanwal; Muhammad Farhan; Rahmatullah Qureshi; Tauseef Anwar; Huma Qureshi; Shujat Ali; Hossam S. El-Beltagi; Dilbar Bazarbayeva; Ibtisam M. Alsudays; Khalid H. Alamer; et al. (Environmental Monitoring and Assessment, 2026)

Retraction notice to “Borage leaf extract improves the vase life of cut gladiolus flowers by delaying the senescence process and reducing water stress” [Postharvest Biol. Technol. 210 (2024) 112766] - Faisal Zulfiqar; Anam Moosa; Antonio Ferrante; Anastasios Darras; Mohamed S. Sheteiwy; Baber Ali; Muhammad Ahsan Altaf; Walid Soufan; Ayman El Sabagh (Postharvest Biology and Technology, 2026)

Bacterial Metabolite-Derived NDM-1 Inhibitors: A Computational Strategy to Overcome β-Lactam Resistance - Bader S. Alotaibi; Farhat Shabbir; Muhammad Umer Khan; Iqra Ahmad; Hira Khalid; Shahid Aziz; Abid Ali; Sonia Younas; Hanna Dib; Khaled Fahmi Fawy; Umar Nishan; Mohibullah Shah (Probiotics and Antimicrobial Proteins, 2026)

Retraction Note: Morphological and genetic diversity of barley (Hordeum vulgare L.) germplasm - Ayaz Ali; Rahman Ullah; Saeed Anwar; Ahmad Ali; Zahid Ullah; Hassan Sher; Javed Iqbal; Banzeer Ahsan Abbasi; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Mechanical power for ventilation - looking beyond the lung - Mutaz I. Othman; Majd M. AlBarakat; Ahmed S. Mohamed; Syed Muhammad Hassan; Rebecca R. George; Ahmad A. Omari; Emad M. Mustafa; Ali Ait Hssain; Hana J. Abukhadijah; Abdulqadir J. Nashwan (Next Research, 2026)

Facile fabrication of NiO/MnO2/CuO nanocomposite as robust electrode material for electrochemical water splitting - Atif Nazir; Chanda Sehar; Muhammad Fahad Saeed; Areej Fatima; Wael dheaa Kadhim; Zainab Ahmed Abass; Imran Shakir; Aboud Ahmed Awadh Bahajjaj; Muhammad Ali Khan; S. Shah (Fuel, 2026)

Experimental investigation of the mechanical and thermal behaviors of shear connectors in concrete sandwich panels - Madyan A. Al-Shugaa; Khalid Mohamed; Abubakr E. S. Musa; Amin Al-Fakih; Ridha A. A. Alhasan; Mohammed A. Al-Osta; Muhammad K. Rahman; Mohammed Rizwan Ali (Innovative Infrastructure Solutions, 2026)

Polyphenol-based therapeutics for glioblastoma: validation from In-vitro cell viability assay and integrated onco-omics computational analysis - Yogesh H S; Sadik Shaik; Sibghatullah Muhammad Ali Sangi; Krishna Swaroop; Sreeharsha Nagaraja; Anitha K N; Vipin Kumar Mishra; Santosh Prasad Chaudhary Kurmi; Subrata Nath; Shankar Thapa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Integrating organic and inorganic amendments to enhance wheat growth, physiology and antioxidant activity while reducing cadmium accumulation - Ahmad Ali; Zaffar Malik; Muhammad Abdul Basit; Abubakar Dar; Usman Zulfiqar; Dilnoza Sotiboldiyeva; Muydinjon Muminov; Hossam S. El-Beltagi; Mashael Daghash Alqahtani (BioMetals, 2026)

Marine Drug Design for Epitheliocytis Rendering AI ‐Assisted Bioisosteric Replacement of Salicin - Muhammad Naveed; Khushbakht Javed; Tariq Aziz; Rahmana Wazir; Imran Ali; Ayaz Ali Khan; Ashwag Shami; Maher S. Alwethaynani; Fahad Al‐Asmari; Fakhria A. Al‐Joufi (Journal of Fish Diseases, 2026)
Epitheliocystis is a distinctive and relatively understudied bacterial infection of finfish skin and gill epithelia that occurs intracellularly and results in the enlargement of the host cells. The Candidatus Syngnamydia salmonis is a bacterial pathogen that affects fish, especially salmon species like trout and salmon. The production of Epitheliocystis by Candidatus Syngnamydia salmonis poses several challenges to the aquaculture industry. Currently, limited drugs and therapies are available to effectively manage and cease the spread of this disease. The goal of this study was to develop a potential drug target for the treatment of epitheliocystis. Salicin, an organic glucoside widely known for its anti‐inflammatory characteristics, was chosen as the initial compound because of its pharmacological significance and confirmed as a bioisostere (a compound with identical biological activities but a different structure). The Xundrug MolOpt AI generative model of bioisosteric replacement tool was chosen as the optimisation technique in a cognitive exertion to improve the novel drug candidate salicin by its AI‐assisted bioisosteric replacement. To retrieve the docking results, the top three ligands from Xundrug and the cell division protein of Candidatus Syngnamydia salmonis were uploaded to the HDOCK web server, which utilises a hybrid docking technique combining template‐based modelling for docking. The target drug candidate was selected based on model 17's highest docking score of 135.6 kcal/mol. Furthermore, the Lipinski rule of five and the ADMET properties of the Bioisosteric Replaced Salicin model 17 (BRS‐17) were carefully explored. The results showed that BRS‐17 fulfilled the pharmacophore characteristics criteria, hence making it an ideal target candidate for Candidatus Syngnamydia salmonis' cell division protein. Additionally, the results are supported by −6.735Kcal/mol docking score predicted by DockThor. With the help of the supporting information from this study, the proposed drug design can close the gap in earlier studies for resistance to antibiotic treatments. It is suggested that in vitro tests be performed on this drug to show the effectiveness of the suggested design.

Sediment transport modeling of trenching activities: a case study for the Safaniya coastal waters in the Arabian Gulf - Abdul Azeez Saleem; Akurathi V. S. Chaitanya; Salim Lateef; Jiya Albert; Muhammad Shafeeque; Karuppasamy P. Manikandan; Thadickal V. Joydas; Mohamed Asharaf; Luai M Alhems; Ali M. Qasem; Sabique Langodan; Diego Lozano-Cortés (Ocean Dynamics, 2026)

Exploring smart solutions for stressed soils: dual-action of culture filtrates and nanoparticles for sustainable onion cultivation - Muhammad Imran; Maryam M. Alomran; Hanan A. Khalifa; Muhammad Saqib Bilal; Atef F. Ahmed; Esmat F. Ali; Abeer S. Alqurashi; Munirah F. Aldayel; Kamal A. M. Abo-Elyousr (European Journal of Plant Pathology, 2026)

Mitigating cadmium-stressed spinach by the synergistic effect of vermicompost and selenium: associated heath risks assessment - Taiba Rauf; Kamran Ashraf; Zeeshan Ahmed; Rabiya Nasir; Muhammad Zeeshan Mansha; Qamar uz Zaman; Ghulam Murtaza; M. Ajmal Ali; Mohamed S. Elshikh; Rashid Iqbal; Lala Gurbanova; Nazim S. Gruda (Environmental Geochemistry and Health, 2026)

Investigating the Wound Healing Potential of CuCO3 Nanoparticles in Alloxan-Induced Diabetic Albino Mice: An Experimental and In Silico Approach - Muhammad Saqib Rafiq; Jabbir Ali Khan; Ashfaq Ahmad Shah Bukhari; Samra Shafqat; Ahmad Waheed; Muhammad Yasir Abbas; Muhammad Waseem Aslam; Imran Ibrahim Shaikh; Khalid S. Almaary; Muhammad Saleem Khan (Biological Trace Element Research, 2025)

Investigating the taxonomic scope of Meliolales species–host relationships and geographic trend - Muhammad Binyamin Khan; Abdul Wahab; Sana; Sardar Ali; De-Ping Wei; Marasinghe Wadige Diana Sandamali; S. Hongsanan; Xiang-Yu Zeng; Muhammad Ishaq; Munazza Kiran; Ting Chi Wen (New Zealand Journal of Botany, 2025)

Assessment of soil biological quality under long-term rice-wheat cropping system: Effect of continuous vs. residual organic nutrient inputs - Loitongbam Joymati Chanu; Tapan Jyoti Purakayastha; Debarati Bhaduri; Muhammad Fraz Ali; Yashbir S. Shivay; Samapti Saren; Vikas Kumar; Majid Alhomrani; Abdulhakeem S. Alamri (Soil and Tillage Research, 2025)

Exploring the therapeutic potential of Nasturtium microphyllum (Boenn.) Rchb.: a combined in-vitro, in-vivo and in-silico approach - Rabia Khan; Muhammad Musa; Syed Mubassir Shah; Hussan Ara Begum; Alaa S. Alhegaili; Sajid Hussain; Atif Ali Khan Khalil; Sajid Ali (Inflammopharmacology, 2025)

Correction to: Lineament Extraction via Satellite Imagery for a Seismic Zone in the Sarpol Zahab Region - Randa Ali; Xiyong Wu; Qiang Chen; Basheer A. Elubid; Dafalla S. Dafalla; Muhammad Kamran; Abdelmottaleb A. Aldoud (Remote Sensing in Earth Systems Sciences, 2025)

Ex-situ multi-media bioleaching and functional characterization of indigenous fungal strains for chromium and zinc remediation in polluted soils - Ibrar Khan; Muhammad Bilal Akram; Aneela Rehman; Mujaddad Ur Rehman; Tawaf Ali Shah; Saad A. Alamri; Yasser S. Mostafa; Abdulrahman A. Almehizia (Biodegradation, 2025)

Mitigating Fruit Drop Challenges: Unraveling the Role of Plant Growth Regulators and Micronutrients in Jujube (Ziziphus mauritiana L.) cvs. in the Cholistan Desert, Pakistan - Abdul Haseeb Ahmed; Rashad Qadri; Khalid Hussain; Muhammad Tahir Akram; Muhammad Azam; Muhammad Awais Ghani; Muhammad Mumtaz Khan; Muhammad Asif Rai; Basharat Ali; Abd El-Zaher M. A. Mustafa; Mohamed S Elshikh; Ghulam Murtaza; et al. (Applied Fruit Science, 2025)

Retraction notice to “Recent advancement challenges with synthesis of biocompatible hemodialysis membranes” [Chemosphere 307, November 2022, 135626] - Shafiq Uz Zaman; Sikander Rafiq; Abulhassan Ali; Muhammad Shozab Mehdi; Amber Arshad; Saif-ur Rehman; Nawshad Muhammad; Muhammad Irfan; Muhammad Shahzad Khurram; Muhammad Khaliq U. Zaman; Abdulkader S. Hanbazazah; Hooi Ren Lim; et al. (Chemosphere, 2025)

Comprehensive Molecular Profiling of AcrAB-TolC Efflux Pump Genes in Salmonella typhi Isolates from Typhoid Infected Patients - Muhammad; Sadiq Azam; Noor Rehman; Alaa S. Alhegaili; Ibrar Khan; Aakash Ahmad; Atif Ali Khan Khalil; Sajid Ali (Current Microbiology, 2025)

Sustainable kaolin-crosslinked kappa-carrageenan hydrogel as an efficient adsorbent for cationic dye removal from wastewater - Fekri Abdulraqeb Ahmed Ali; Javed Alam; Ahmed S. Al-Fatesh; Farid Fadhillah; Badr M. Thamer; Muhammad Ali Shar; Mansour Alhoshan (Journal of Water Process Engineering, 2025)

Maize/Legume Intercropping Increases Nutrient Uptake, Crop Yields, Land Productivity, and Economic Profits in Resource-intensive Arid-irrigated Areas - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Ghulam Abbas Shah; Wang Zhiqi; Muhammad Jawad Hassan; Muhammad Bilal; Harun Gitari; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Adsorption of 4-bromophenol from simulated wastewater using magnetic carbon-based composites: Kinetics, equilibrium, thermodynamics, and density functional theory analysis - Beatris L. Mello; Pascal S. Thue; Ali Hamid; Muhammad Usama; Fernando Machado Machado; Moaaz K. Seliem; Younes Dehmani; Glaydson S. dos Reis; Mohamed Abdel Salam; Hammad Khan; Luis F.O. Silva; Eder C. Lima (Journal of Water Process Engineering, 2025)

Femtosecond laser-structured waste cardboard: Simultaneously separating oil/water emulsions and removing viscous oil with solar energy - Muhammad Qasim; Hamzeh Sabouni; Ganjaboy S. Boltaev; Ali S. Alnaser (Journal of Cleaner Production, 2025)

Urease inhibitory compounds from the stem bark of Parinari excelsa sabine and their chemophenetic significance - Alain W. Ngouonpe; Joseph Tchamgoue; Alain Tadjong Tcho; Bruno Dupon A. Ambamba; Muhammad S. Ali; Mehreen Lateef; Simeon F. Kouam (Biochemical Systematics and Ecology, 2025)

Regulation of Apoptotic Pathways by MicroRNAs: A Therapeutic Strategy for Alzheimer’s Disease - Mohamed J. Saadh; Faris Anad Muhammad; Tuqa S. Alazzawi; Ali A. Fahdil; Zainab H. Athab; Jamshid Tuxtayev; Fahad Alsaikhan; Bagher Farhood (Molecular Neurobiology, 2025)

Green-Synthesized ZnO Nanoparticles Using Methanolic Extract of Moringa oleifera Leaves: Characterization and Evaluation of Wound Healing Efficacy - Mazhar Abbas; Aqsa Mumtaz; Osama A. Mohammed; Kinza Zafar; Ishtiaq Ahmed; Muhammad T. Iqbal; Munawar Iqbal; Arif Nazir; Ali M. S. Eleragi; Lobna A. Saleh; Mohammed A. Attia; Emad Bahashwan; et al. (Journal of Pharmaceutical Innovation, 2025)

Long-term PM2.5 exposure in Bangladesh: identification of pollution hotspots, trends, sources and health risk assessment - Md. Arfan Ali; Mazen E. Assiri; Muhammad Bilal; Salman Tariq; Gerrit de Leeuw; M. Nazrul Islam; Yu Wang; Lama Alamri; Ayman S. Ghulam; Shamsuddin Shahid (Air Quality, Atmosphere & Health, 2025)

Selecting the best CMIP6 GCMs for application and downscaling studies over Pakistan, Nepal and Bangladesh - Shaukat Ali; Michelle Simões Reboita; Zulfiqar A. Bhutta; Muhammad Arif Goheer; Joao Gabriel Martins Ribeiro; Christie André de Souza; Glauber Willian Ferreira; Jai Das; Rida S. Kiani; Azfar Hussain; Fatima Saeed; Muhammad Adnan Abid; et al. (Acta Geophysica, 2025)

New insights on the potentiality of deep learning techniques in supporting the assessment of some biotic diseases on maize - Sajjad Hussain Qureshi; Sohail Raza Chohan; Muhammad Usman; Muhammad Luqman; Mueen Alam Khan; Baber Ali; Reem M. Aljowaie; Mohamed S. Elshikh; Rashid Iqbal (Journal of Plant Pathology, 2025)

An overview of ethnobotanical investigations for primary healthcare: a case study from Mardan district, Pakistan - Muhammad Mohsin; Musheerul Hassan; Ivana Vitasović-Kosić; Mona S. Alwahibi; Sher Wali; Qoryog’diyev Zufar Oxunjonovich; Muhammad Abdul Aziz; M. Ajmal Ali; Rainer W. Bussmann; Arshad Mehmood Abbasi (Plant Biosystems, 2025)

Fluoride contamination in plum and peach orchards and its impact on earthworm growth and reproduction - Muhammad Nauman Ahmad; Shah Saud; Afia Zia; Muhammad Baseer Us Salam; Somaira Bibi; Ayaz AlI Khan; Tariq Aziz; Saleh A. Alghamdi; Abdulhakeem S. Alamri; Majid Alhomrani (Environmental Monitoring and Assessment, 2025)

Assessment of Exploited Stock and Management Implications of Tiger Tooth Croaker (Otolithes ruber) in Coastal Waters of Makran, Pakistan - Samroz Majeed; S M Nurul Amin; Asad Ullah Ali Muhammad; Sudheer Ahmed (Fishes, 2025)
Pakistan’s marine fishing industry is crucial to the country’s economy, generating employment opportunities and foreign revenue. It produces 80% of the country’s total fish production. Otolithes ruber is a commercially important fish on the Makran coast of Pakistan, contributing significantly to the region’s croaker fisheries. This study is the first to apply three length-based approaches for assessing the stock status of O. ruber in the Makran coast: (1) TropFishR to estimate the mortality, growth parameters, and current exploitation status, reference points based on the yield per recruitment model, (2) the length-based Bayesian biomass method (LBB) to calculate stock biomass, and (3) the length-based spawning potential ratio (LBSPR) to estimate the spawning potential ratio. The length–weight relationship of Otolithes ruber was a positive allometric pattern (b = 3.28; R2 = 0.94). Growth parameters for Otolithes ruber were L∞ = 55.47 cm, K = 0.50 year−1. The calculated total mortality rate (Z), natural mortality (M), and fishing mortality (F) were 2.27 year−1, 0.67 year−1, and 1.6 year−1, respectively. The exploitation rate (E) was 0.70, indicating severe overexploitation. The current length at first capture (Lc50) = 27.37 cm was lower than that at first maturity (Lm50) = 30.75 cm, indicating growth overfishing. The current spawning potential ratio (8%) was lower than the optimal value (40%), indicating recruitment overfishing. The current biomass, concerning virgin biomass B/Bo, was also 8%, resulting in a 92% stock decline. We recommend reducing the exploitation pressure by limiting the commercial catch to an optimum length range of 34.5–42.2 cm and reducing fishing pressure by 40% to ensure sustainable fishery management.

Managing anthracnose fruit rot disease in pepper caused by Colletotrichum capsici via potash alum and frankincense essential oil - Mansour M. El-Fawy; Muhammad Imran; Esmat F. Ali; Abeer S. Alqurashi; Ahmed A. Issa; Rabee A. Emam; Mohamed F. Abd El-Mageed; Najeeb M. Almasoudi; Nashwa M. A. Sallam; Kamal A. M. Abo-Elyousr (Journal of Plant Pathology, 2025)

Spatio‐Temporal Dynamics of Vegetation and Land Surface Temperature in Saudi Arabia: Impacts of Climate Change on Agricultural Sites From 2010 to 2023 - Mazen E. Assiri; Md. Arfan Ali; Lama Alamri; Muhammad Haroon Siddiqui; Ayman S. Ghulam; Shamsuddin Shahid (International Journal of Climatology, 2025)
Saudi Arabia has one of the greatest water shortages and the least vegetation in the world, which is potentially exacerbating the issue of environmental impacts. Therefore, it is crucial to understand the interaction between climate change, vegetation dynamics and land surface temperature (LST). The present study investigates the spatio‐temporal distributions, variations, change detection and trends of vegetation dynamics and surface temperature over eight agricultural sites in Saudi Arabia using the Normalised Difference Vegetation Index (NDVI) and LST from Landsat 7 (Enhance Thematic Mapper Plus: ETM + ) and Landsat 8 (operational land imager: OLI) measurements for the period 2010–2023. The study also examined the relationship between NDVI, LST and climate variables such as air temperature, rainfall, relative humidity and soil moisture. Results showed that an NDVI > 0.20 represents vegetation in Saudi Arabia. Higher values of NDVI were found in Baysh, Jazan province, compared to other agricultural sites. Significant annual and seasonal variations in NDVI were also observed across eight major agricultural sites in Saudi Arabia, attributable to the region's varying climate conditions. Vegetation expansion in 2023 exceeded that in 2014 in Buraydah (304.34 km 2 ), Tabarjal (63.81 km 2 ), Hail (33.20 km 2 ), Al Qirw (22.53 km 2 ) and Baysh (3.07 km 2 ), while reductions were noted in Wadi Al Dawasir (274.58 km 2 ), Tabuk (88.56 km 2 ) and Al Ahsa (27.30 km 2 ). The LST over soil and vegetated surfaces showed that vegetation notably reduced LST at Hail (3.14°C), Al Ahsa and Wadi Al Dawasir (5.43°C), Buraydah (4.53°C), Baysh (2.71°C), Al Qirw (5.17°C), Tabuk (6.24°C) and Tabarjal (3.13°C). The study found that NDVI, LST and climate variables are positively and negatively correlated, which indicates a significant impact of climate change on vegetation patterns. The findings of this study are highly relevant for informing agricultural and environmental policy development in Saudi Arabia, with a focus on enhancing vegetation cover, mitigating the impacts of rising temperatures and advancing sustainable agricultural practices to address the challenges posed by climate change.

Yield gains and resource use advantages driven by legume choice and row ratio in cotton/legume intercropping under arid-irrigated conditions - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Amjad Saeed; Aqib Mehmood; Sana Ur Rehman; Zafar Iqbal; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; Ghulam Abbas Shah; et al. (Field Crops Research, 2025)

Assessing access to safe drinking water in flood-affected areas of District Nowshera, Pakistan: A case study towards achieving sustainable development goal 6.1 - Muhammad Tufail; Muhammad Jamal Nasir; Aqil Tariq; Zahid Ali; Saad S. Alarifi (Ecohydrology & Hydrobiology, 2025)

Association mapping of leaf rust disease resistance and yield related traits in bread wheat using a high density 90K SNP array - Muhammad Rauf Shah; Muhammad Ali Sher; Salma Bashir; Muhammad Zeshan Zafer; Douglas Law; Sania Begum; Nasr Ullah Khan; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Daniel K. Y. Tan; Muhammad Yasin (Journal of Plant Diseases and Protection, 2025)

The role of VEGF in vascular dementia: impact of aging and cellular senescence - Neetu Agrawal; Muhammad Afzal; Nawaid Hussain Khan; Subbulakshmi Ganesan; Mukesh Kumari; S. Sunitha; Aniruddh Dash; Kavita Goyal; Brajgopal Kushwaha; A. Rekha; Mohit Rana; Haider Ali (Biogerontology, 2025)

From protein to immunology: comprehensive insights into Marburg virus vaccines, mechanism, and application - Mohamed J. Saadh; Faris Anad Muhammad; Rafid Jihad Albadr; Gaurav Sanghvi; S. Renuka Jyothi; Mayank Kundlas; Kamal Kant Joshi; Surat Gulyamov; Waam Mohammed Taher; Mariem Alwan; Mahmood Jasem Jawad; Ali M. Ali Al-Nuaimi (Archives of Microbiology, 2025)

Visible light active CdS/CuO nanocomposites for photocatalytic degradation of ciprofloxacin, H2 production and antimicrobial activity - Naveed Akhtar; Chaejin Choi; Muhammad Ateeq; Perveen Fazil; Noor S. Shah; Javed Ali Khan; Abdullah G. Al-Sehemi; Amir Zada; Muhammad Ishaq Ali Shah; Rabia Ikram; Changseok Han (Chemical Engineering Journal, 2025)

RETRACTED ARTICLE: ArticleNoteMorphological and genetic diversity of barley (Hordeum vulgare L.) germplasm - Ayaz Ali; Rahman Ullah; Saeed Anwar; Ahmad Ali; Zahid Ullah; Hassan Sher; Javed Iqbal; Banzeer Ahsan Abbasi; Dunia A. Al Farraj; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Exogenous application of melatonin and jasmonic acid protects the sugar beet from heat stress by modulating the enzymatic antioxidants deference mechanism and accumulation of organic osmolytes - Muhammad Irfan; Ahmed Abou El-Yazied; Muhammad Sheeraz; Shabir Hussain; Abdul Sattar; Qasim Ali; Hany G. Abd El-Gawad; Fahad Mohammed Alzuaibr; Maha Mohammed Alharbi; Siham M. Al-Balawi; Doaa Bahaa Eldin Darwish; Eldessoky S. Dessoky; et al. (Acta Physiologiae Plantarum, 2025)

Unfolding the role of silicon dioxide nanoparticles (SiO2NPs) in inducing drought stress tolerance in Hordeum vulgare through modulation of root metabolic, nutritional, and hormonal profiles - Nadiyah M. Alabdallah; Khansa Saleem; Aisha Saud Al-Shammari; Saleha S. AlZahrani; Ali Raza; Muhammad Ahsan Asghar; Hafiz Hassan Javed; Jean Wan Hong Yong (South African Journal of Botany, 2025)

Maximizing heavy metal removal and precious metal recovery with innovative biowaste-derived biosorbents and biochar - Behzad Murtaza; Roshina Arshad; Moon Kinza; Jianxu Wang; Muhammad Shahid; Muhammad Imran; Noor S. Shah; Qasim Ali; Jibran Iqbal; Changseok Han (Process Safety and Environmental Protection, 2025)

Biomitigation of noxious metal ions using engineered lignin-based nanocomposites for sustainable environment - Zaeem Bin Babar; Rashid Iftikhar; Komal Rizwan; Shahid Munir; Mashhood Urfi; Fawad Ashraf; Muhammad Ali Inam; Shahid Iqbal; Muhammad Saad; Sajid Mahmood; Nasser S. Awwad; Hala A. Ibrahium (Journal of Water Process Engineering, 2025)

Amine-functionalized organically modified silica for the effective adsorption of Chlorpyrifos and Triazophos Residues from Orange juice - Muhammad Hayat; Suryyia Manzoor; Nadeem Raza; Hina Raza; Ayesha Javid; Zeeshan Ali; Muhammad Imran Khan; Faisal K. Algethami; Najla AlMasoud; Taghrid S. Alomar (Food Chemistry, 2025)

Moringa Biopriming with Zn Spray Improved Nutrients Rich Biofortified Chickpea Grains and Drought Tolerance at Reproductive Stages Under Arid Environment - Hamid Nawaz; Malik Muhammad Yousaf; Nazim Hussain; Tanveer Hussain; Malik Waqar Yousaf; Malik Ibrar Yousaf; Mona S. Alwahibi; Mohamed S. Elshikh; Baber Ali; Rashid Iqbal (Journal of Crop Health, 2025)

Histological analysis of petiole structure in Euphorbiaceae species for taxonomic classification - Salman Majeed; Muhammad Zafar; Mohamed S. Elshikh; M. Ajmal Ali; Mushtaq Ahmad; Asif Mir; Trobjon Makhkamov; Mohammad Athar; Sokhib Islamov; Moona Nazish; Khislat Khaydarov; Maxsuda Nizomova; et al. (Genetic Resources and Crop Evolution, 2025)

Targeting senescence and GATA4 in age-related cardiovascular disease: a comprehensive approach - Mohd Imran; Abdulmalik S. A. Altamimi; Muhammad Afzal; M. Arockia Babu; Kavita Goyal; Suhas Ballal; Pawan Sharma; Fadiyah Jadid Alanazi; Abeer Nuwayfi Alruwaili; Nouf Afit Aldhafeeri; Haider Ali (Biogerontology, 2025)

In Silico Comparison of WRKY Transcription Factors in Wild and Cultivated Soybean and Their Co-expression Network Arbitrating Disease Resistance - Muhammad Amjad Nawaz; Hafiz Kashif Khalil; Farrukh Azeem; Muhammad Amjad Ali; Igor Eduardovich Pamirsky; Kirill S. Golokhvast; Seung Hwan Yang; Rana Muhammad Atif; Gyuhwa Chung (Biochemical Genetics, 2025)

Effects of Tribulus terrestris extract and 17 α-methyl testosterone on masculinization, growth, economic efficiency and health assessment of Nile tilapia (Oreochromis niloticus) - Habib Ul Hassan; Amjad Ali; Basim S. A. Al Sulivany; Muhammad Kabir; Roohi Kanwal; Mohammad Z. Ahmed; Rizwana Abdul Ghaffar; Meer Zeeshan Ijaz; Naseem Rafiq; Mary Mahwish; Mohammad Abdul Momin Siddique (Aquaculture International, 2025)

Dust over Saudi Arabia from multisource data: case studies in winter and spring - Mazen E. Assiri; M. Nazrul Islam; Md Arfan Ali; Arjan O. Zamreeq; Ayman S. Ghulam; Muhammad Ismail (Air Quality, Atmosphere & Health, 2025)

Impact of Indonesia's Forest Management Units on the reduction of forest loss and forest fires in Sulawesi - Colas Chervier; Stibniati S. Atmadja; Sandy Nofyanza; Choiriatun Nur Annisa; Fitri Nurfatriani; Rochadi Kristiningrum; Muhammad Alif K. Sahide; Ali Suhardiman; Syukur Umar (Ecological Economics, 2025)

Leveraging machine learning to model salinity and water flux for improved insights into forward osmosis membrane bioreactors - Ali Aldrees; Bilal Siddiq; Wael S. Al-Rashed; Muhammad Faisal Javed; Majid Khan (Journal of Water Process Engineering, 2024)

Two-dimensional MXene based innovative electrode materials for supercapacitors: Recent advances and prospects - Salamat Ali; Muhammad Ahsan Farooq Qaisar; Muhammad Sufyan Javed; Khalid Umer; Saleh S. Alarfaji; Muhammad Mateen; Muhammad Chhattal; Shafqat Ali; Anand Parkash; Tensangmu Lama Tamang; Jing Qi (Fuel, 2024)

Characterisation of the essential oil from Iphiona grantioides and investigation of its antibacterial and antioxidant properties - Shah Iram Niaz; Muhammad Ali; Muhammad Saleem; Rubina Qaisrani; Kamran Safdar; Malik Muhammad Akram; Abdur Rauf; Maqbool Ahmad; Sanaullah Abbasi; Taghrid S. Alomar; Najla AlMasoud; Giovanni Ribaudo (Natural Product Research, 2024)

Effectiveness of biochar and wood vinegar from guava trees in controlling Fusarium verticillioides and enhancing growth and anatomical traits of maize (Zea mays L.) - Mansour M. El-Fawy; Ayman S. Saeed; Mohamed K. Abou-Shlell; Mahmoud A. Soliman; Esmat F. Ali; Ahmed A. Issa; Kamal A. M. Abo-Elyousr; Muhammad Imran; Asmaa S. El-Nagar (Journal of Plant Diseases and Protection, 2024)

Nitrogen and carbohydrate metabolisms are key factors in maize (Zea mays L.) germination under chromium-induced ROS - Muhammad Imran Atta; Syeda Sadaf Zehra; Zhihang Zhuo; Habib Ali; Malik Waseem Abbas; Syed Naveed Abbas; Sadia Sarwar; Fatima Muneer; Irfan Ahmad; Danpping Xu; Hasham S. Almoallim; Mohammad Javed Ansari (Journal of Plant Diseases and Protection, 2024)

Lineament Extraction via Satellite Imagery for a Seismic Zone in the Sarpol Zahab Region - Randa Ali; Xiyong Wu; Qiang Chen; Basheer A. Elubid; Dafalla S. Dafalla; Muhammad Kamran; Abdelmottaleb A. Aldoud (Remote Sensing in Earth Systems Sciences, 2024)

Hypoxia stress: plant’s sensing, responses, and tolerance mechanisms - Farwa Basit; Muhammad Khalid; Ali El-Keblawy; Mohamed S. Sheteiwy; Saad Sulieman; Izabela Josko; Faisal Zulfiqar (Environmental Science and Pollution Research, 2024)

Remote Sensing Assessment of Water Resources, Vegetation, and Land Surface Temperature in Eastern Saudi Arabia: Identification, Variability, and Trends - Mazen E. Assiri; Md Arfan Ali; Muhammad Haroon Siddiqui; Albandari AlZahrani; Lama Alamri; Abdullah Masoud Alqahtani; Ayman S. Ghulam (Remote Sensing Applications: Society and Environment, 2024)

In silico genome-wide analysis of the growth-regulating factor gene family and their expression profiling in Vitis vinifera under biotic stress - Nimra Nazir; Azhar Iqbal; Hadia Hussain; Faisal Ali; Khalid S. Almaary; Most. Nazmin Aktar; Muhammad Sajid; Mohammed Bourhia; Ahmad Mohammad Salamatullah (Cell Biochemistry and Biophysics, 2024)

Prediction of surface urban heat island based on predicted consequences of urban sprawl using deep learning: A way forward for a sustainable environment - Shun Fu; Lufeng Wang; Umer Khalil; Ali Hassan Cheema; Israr Ullah; Bilal Aslam; Aqil Tariq; Muhammad Aslam; Saad S. Alarifi (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Identification of natural potent inhibitors against Mycobacterium tuberculosis isocitrate lyase: an in silico study - Ali A. Rabaan; Muhammad A. Halwani; Mohammed Garout; Safaa A. Turkistani; Roua A. Alsubki; Abdulsalam Alawfi; Amer Alshengeti; Mustafa A. Najim; Nawal A. Al Kaabi; Thikrayat Q. Alqazih; Ali A. Aseeri; Afnan S. Bahitham; et al. (Molecular Diversity, 2024)

Low doses of entomopathogens matter hugely, gateway to resistance development and retarded growth in Helicoverpa armigera - Mirza Abdul Qayyum; Zhuo Zhihang; Waqas Wakil; Habib Ali; Abid Ali; Muhammad Usman Ghazanfar; Muhammad Yasin; Xu Danping; Hasham S. Almoallim; Mohammad Javed Ansari; Muhammad Tahir; Kashif Ali; et al. (Journal of Plant Diseases and Protection, 2024)

Exploring the tectono-magmatic evolution of intraoceanic fore-arc setting during subduction initiation: perspectives from trace and platinum group element systematics of the Jijal ultramafic arc system, NE Pakistan - Tehseen Zafar; Hafiz Ur Rehman; Irfan Maqbool Bhat; Zaheen Ullah; Muhammad Farhan; Abiola Oyebamiji; Fatemeh Nouri; Fatemeh Spedibar; Shuguang Song; Zahid Hussain; Mubasir Ali; Cheng-Biao Leng; et al. (International Geology Review, 2024)

Mineral Metamorphosis: Tracing the static and dynamic nexus between minerals and global south markets - Shoaib Ali; Muhammad Naveed; Nassar S. Al-Nassar; Nawazish Mirza (Resources Policy, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Numerical investigation of vortex-induced vibrations (VIV) of a rotating cylinder in in-line and cross-flow directions subjected to oscillatory flow - Ubaid Ur Rehman; Adnan Munir; Niaz Bahadur Khan; Ming Zhao; Muhammad Kashif; Mohammad S. Islam; Zeeshan Saeed; Mian Ashfaq Ali (Ocean Engineering, 2024)

A Theoretical Investigation for Exploring the Potential Performance of Non-Fullerene Organic Solar Cells Through Side-Chain Engineering Having Diphenylamino Groups to Enhance Photovoltaic Properties - Fakhar Abbas; R. Bousbih; Ali Raza Ayub; Saba Zahid; Mohammed Aljohani; Mohammed A. Amin; Muhammad Waqas; Mohamed S. Soliman; Rasheed Ahmad Khera; Nazish Jahan (Journal of Fluorescence, 2024)

Miniaturizing Power: Harnessing Micro-Supercapacitors for advanced micro-electronics - Qazi Muhammad Saqib; Abdul Mannan; Muhammad Noman; Mahesh Y. Chougale; Chandrashekhar S. Patil; Youngbin Ko; Jungmin Kim; Swapnil R. Patil; Muhammad Yousuf; Rayyan Ali Shaukat; Young Pyo Jeon; Deepak Dubal; et al. (Chemical Engineering Journal, 2024)

Unveiling the mechanisms of silicon-induced salinity stress tolerance in Panicum turgidum: Insights from antioxidant defense system and comprehensive metabolic and nutritional profiling - Nadiyah M. Alabdallah; Aisha Saud Al-Shammari; Khansa Saleem; Saleha S. AlZahrani; Ali Raza; Muhammad Ahsan Asghar; Abd Ullah; Muhammad Iftikhar Hussain; Jean Wan Hong Yong (South African Journal of Botany, 2024)

Hierarchical S-scheme heterojunction systems: A comprehensive review on outstanding photocatalysts - Huimin Han; Muhammad Raheel Khan; Irshad Ahmad; Ayman Al-Qattan; Ijaz Ali; Md Rezaul Karim; Hossein Bayahia; Farhat S. Khan; Zubair Ahmad; Saad Ullah (Journal of Water Process Engineering, 2024)

Trapping the genetic variation for yield and yield related attributes in bread wheat under water deficit stress - Hafiz Ghulam Muhu-Din Ahmed; Muhammad Naeem; Yawen Zeng; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Noor Fatima; Ibtasam Moeez; Hayssam M. Ali; Nagy S. Radwan; Sezai Ercisli; et al. (Euphytica, 2024)

RETRACTED: Borage leaf extract improves the vase life of cut gladiolus flowers by delaying the senescence process and reducing water stress - Faisal Zulfiqar; Anam Moosa; Antonio Ferrante; Anastasios Darras; Mohamed S. Sheteiwy; Baber Ali; Muhammad Ahsan Altaf; Walid Soufan; Ayman El Sabagh (Postharvest Biology and Technology, 2024)

Exercise Improves Cerebral Blood Flow and Functional Outcomes in an Experimental Mouse Model of Vascular Cognitive Impairment and Dementia (VCID) - Mohammad Badruzzaman Khan; Haroon Alam; Shahneela Siddiqui; Muhammad Fasih Shaikh; Abhinav Sharma; Amna Rehman; Babak Baban; Ali S. Arbab; David C. Hess (Translational Stroke Research, 2024)

Zinc and amino acids improve the growth, physiological, and biochemical attributes of corn under different irrigation levels - Ayman M.S. Elshamly; Rashid Iqbal; Baber Ali; Iftikhar Ahmed; Muhammad Irfan Akram; Shehzad Ali; Allah Ditta; Fatih ÇIĞ; Mohamed S. Elshikh; Abd El-Zaher M.A. Mustafa; Mahdy H. Hamed (Rhizosphere, 2024)

Correction to: Differential responses of Brassica napus cultivars to dual effects of magnesium oxide nanoparticles - Sharafat Ali; Zaid Ulhassan; Skhawat Ali; Zohaib Kaleem; Muhammad Arslan Yousaf; Mohamed S. Sheteiwy; Shafaqat Ali; Muhammad Waseem; Sanaullah Jalil; Jian Wang; Weijun Zhou (Environmental Science and Pollution Research, 2024)

Pesticide residues in adults living near a bioenergy plant with 85,000 tons of contaminated wetcake - Muhammad Zahid; Jabeen Taiba; Khiara Cox; Ali S. Khan; Terra Uhing; Eleanor Rogan (Chemosphere, 2024)

Geospatial approach in modeling linear, areal, and relief morphometric interactions in Dabus river basin ecology for sustainable water resource management - Tekalign Ketema Bahiru; Adel S. Aldosary; Abdulla - Al Kafy; Muhammad Tauhidur Rahman; Hrithik Nath; S. Kalaivani; Dulal Sarker; Saleh Alsulamy; Khaled Mohamed Khedher; Ahmed Ali A. Shohan; Md Nahid Ferdous; Mohamed Elhag (Groundwater for Sustainable Development, 2024)

Differential responses of Brassica napus cultivars to dual effects of magnesium oxide nanoparticles - Sharafat Ali; Zaid Ulhassan; Skhawat Ali; Zohaib Kaleem; Muhammad Arslan Yousaf; Mohamed S. Sheteiwy; Shafaqat Ali; Muhammad Waseem; Sanaullah Jalil; Jian Wang; Weijun Zhou (Environmental Science and Pollution Research, 2024)

Fundamental opportunities and challenges of nutraceutical noodles enriched with agri-food by-products - Zahoor Ahmed; Jin Chen; Tabussam Tufail; Anam Latif; Muhammad Arif; Riaz Ullah; Ali S. Alqahtani; Bin Xu (Trends in Food Science & Technology, 2024)

Detection of high-risk human papillomavirus infected cervical biopsies samples by immunohistochemical expression of the p16 tumor marker - Muhammad Shafique; Iqra Shoaib; Bilal Aslam; Rabia Khalid; Imrana Tanvir; Muhammad Hidayat Rasool; Tawaf Ali Shah; Khalid S. Almaary; Mohammed Bourhia; Muhammad Usman Qamar (Archives of Microbiology, 2024)

Synthesis of N-doped TiO2 nanoparticles with enhanced photocatalytic activity for 2,4-dichlorophenol degradation and H2 production - Javed Ali Khan; Murtaza Sayed; Noor S. Shah; Sanaullah Khan; Ashfaq Ahmad Khan; Muhammad Sultan; Ammar M. Tighezza; Jibran Iqbal; Grzegorz Boczkaj (Journal of Environmental Chemical Engineering, 2023)

Chemical and mechanical coating of sulfur on baby corn biochar and their role in soil Pb availability, uptake, and growth of tomato under Pb contamination - Jing Ma; Ziyi Hua; Sana Noreen; Zaffar Malik; Muhammad Riaz; Muhamamd Kamran; Shafaqat Ali; Mohamed S. Elshikh; Fu Chen (Environmental Pollution, 2023)

CA/PEG/chitosan membrane incorporated with TiO2 nanoparticles for strengthening and permselectivity membrane for reverse osmosis desalination - Dwiprayogo Wibowo; Faizal Mustapa; S. Selviantori; Muhammad Idris; Amir Mahmud; Maulidiyah Maulidiyah; Muh. Zakir Muzakkar; Akrajas Ali Umar; Muhammad Nurdin (Environmental Nanotechnology, Monitoring & Management, 2023)

Selective formation of fuel BXT compounds from catalytic hydrodeoxygenation of waste biomass over Ni-decorated beta-zeolite - Ola Ismail; Ala Hamid; Labeeb Ali; Toyin Shittu; Mohamed S. Kuttiyathil; Muhammad Z. Iqbal; Abbas Khaleel; Mohammednoor Altarawneh (Bioresource Technology Reports, 2023)

Exploring the hidden treasures of Nitella hyalina: a comprehensive study on its biological compounds, nutritional profile, and unveiling its antimicrobial, antioxidative, and hypoglycemic properties - Muhammad Imran; Arshad Iqbal; Syed Lal Badshah; Imtiaz Ahmad; Ashwag Shami; Baber Ali; Fatema Suliman Alatawi; Mohsen Suliman Alatawi; Yasser S. Mostafa; Saad A. Alamri; Ahlam A. Alalwiat; Majed A. Bajaber (World Journal of Microbiology and Biotechnology, 2023)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Comparison of As removal efficiency and health risks from aqueous solution using as-synthesized Fe0 and Cu0: modelling, kinetics and reusability - Behzad Murtaza; Asad Ali; Muhammad Imran; Abdullah A. Al-Kahtani; Zeid A. ALOthman; Natasha Natasha; Muhammad Shahid; Noor S. Shah; Muhammad Asif Naeem; Sajjad Ahmad; Ghulam Murtaza (Environmental Geochemistry and Health, 2023)

Systematic elucidation of the multi-target pharmacological mechanism of Terminalia arjuna against congestive cardiac failure via network pharmacology and molecular modelling approaches - Aqsa Asghar; Muhammad Qasim; Fatima Noor; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Muhammad Shareef Masoud; Rashid Bhatti; Ahmad Almatroudi; Faris Alrumaihi; Khaled S. Allemailem (Natural Product Research, 2023)

Multiple phases of yttrium-doped molybdenum trioxide nanorods as efficient dye degrader and bactericidal agents with molecular docking analysis - Muhammad Ikram; Tahira Shujah; Anum Shahzadi; Ali Haider; Aqsa Rafique; Anwar Ul-Hamid; Walid Nabgan; Syed Karrar Haider; Thamraa Alshahrani; Mohammed M. Algaradah; S. Amber Yousaf; Junaid Haider (Chemosphere, 2023)

Regulation of proline metabolism, AsA-GSH cycle, cadmium uptake and subcellular distribution in Brassica napus L. under the effect of nano-silicon - Shaopeng Zhao; Muhammad Kamran; Muhamamd Rizwan; Shafaqat Ali; Lei Yan; Mona S. Alwahibi; Mohamed S. Elshikh; Muhammad Riaz (Environmental Pollution, 2023)

Optimization of viscosity of titania nanotubes ethylene glycol/water-based nanofluids using response surface methodology - Abdullah Bin Mahfouz; Abulhassan Ali; Muhammad Mubashir; Abdulkader S. Hanbazazah; Mustafa Alsaady; Pau Loke Show (Fuel, 2023)

Lipoic Acid Positively Regulates Tomato Growth and Yield by Improving Organic Osmolytes and Antioxidant Defense System Under Saline Conditions - Rohina Bashir; Hafiza Naila Ramzan; Saqib Mahmood; Muhammad Awais; Samina Hassan; Muhammad Aqeel; Haifa A. S. Alhaithloul; Tasahil S. Albishi; Sameer H. Qari; Ali Noman (Journal of Soil Science and Plant Nutrition, 2023)

Neem and Castor Oil–Coated Urea Mitigates Salinity Effects in Wheat by Improving Physiological Responses and Plant Homeostasis - Imran Khan; Sadia Muhammad Ali; Muhammad Umer Chattha; Lorenzo Barbanti; Roberta Calone; Athar Mahmood; Tasahil S. Albishi; Muhammad Umair Hassan; Sameer H. Qari (Journal of Soil Science and Plant Nutrition, 2023)
Soil salinity is abiotic stress of growing concern, whose effects can be potentially mitigated by the use of suitable fertilisers. Based on this, an experiment was conducted to determine the role of vegetable oil–coated urea on the performance of wheat ( Triticum aestivum ) under salinity. Neem oil–coated urea (NOCU), castor oil–coated urea (COCU), and normal urea (NU) were compared in wheat plants growing in pots at three soil salinity levels (0, 6, and 12 dS m -1 ). Plant morphology, growth, element contents (Na, Cl, K, and N), and several traits were assessed at the flag leaf stage; biological yield, grain yield, and its components were assessed at maturity. Salinity stunted growth (approximately -50% yield with high salinity vs. control); boosted Na and Cl concentrations while abating K and N concentrations in plant organs; impaired leaf water status; reduced photosynthetic pigments and increased antioxidant activities and osmo-regulating compounds. NOCU and, to a lesser degree, COCU mitigated salinity effects by upgrading antioxidant activities, reducing oxidative stress markers, increasing leaf water status, photosynthetic pigments, and osmo-regulating compounds. However, NOCU under high salinity could only achieve the levels of NU under intermediate salinity. Lastly, NOCU and COCU restricted plant entry of adverse ions (Na and Cl) while increasing K and N accumulation. Vegetable oil–coated urea, namely NOCU, significantly contributed to improving wheat behaviour and final yield under salinity. These outcomes are associated with the two fertilisers’ properties of slow nitrogen release.

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Trehalose: A Key Player in Plant Growth Regulation and Tolerance to Abiotic Stresses - Muhammad Umair Hassan; Muhammad Nawaz; Adnan Noor Shah; Ali Raza; Lorenzo Barbanti; Milan Skalicky; Mohamed Hashem; Marian Brestic; Saurabh Pandey; Saad Alamri; Yasser S. Mostafa; Ayman E. L. Sabagh; et al. (Journal of Plant Growth Regulation, 2023)

Exploration of the bioenergy potential of Dactyloctenium aegyptium through pyrolysis, kinetics, and thermodynamic parameters to produce clean fuels and biochemicals - Hesham Alhumade; Omar S. Alayed; Muhammad Waqas Iqbal; Ayesha Shahid; Tanveer Iqbal; Muhammad Sajjad Ahmad; Ali Elkamel; Yusuf Al-Turki; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf (Fuel, 2023)

Exploration of plant growth promoting traits and regulatory mechanisms of Bacillus anthracis PM21 in enhancing salt stress tolerance in maize - Muhammad Atif Azeem; Fawad Ali; Abid Ullah; Mahmood Iqbal; Kishwar Ali; Dunia A. Al Farraj; Mohamed S. Elshikh; Qirat Naz; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2023)

Corrigendum to ‘Prediction of carbon-dioxide activity coefficient for solubility in ionic liquids using multi-non-linear regression analysis’, Chemosphere, 311, (2023), 1–10, 137102 - Sami-ullah Rather; Azmi M. Shariff; Aliyu Adebayo Sulaimon; Hisham S. Bamufleh; Ali Qasim; Muhammad Saad Khan; Hesham Alhumade; Usman Saeed; Walid M. Alalayah (Chemosphere, 2023)

Ziziphus spina-christi extract-stabilized novel silver nanoparticle synthesis for combating Fusarium oxysporum-causing pepper wilt disease: in vitro and in vivo studies - Amer M. Abdelaziz; Mohammed A. Elshaer; Mohamed A. Abd-Elraheem; Omar M Omar M Ali; Muhammad I. Haggag; Gharieb S. El-Sayyad; Mohamed S. Attia (Archives of Microbiology, 2023)

Prediction of carbon-dioxide activity coefficient for solubility in ionic liquids using multi-non-linear regression analysis. - Sami-ullah Rather; Azmi M. Shariff; Aliyu Adebayo Sulaimon; Hisham S. Bamufleh; Ali Qasim; Muhammad Saad Khan; Hesham Alhumade; Usman Saeed; Walid M. Alalayah (Chemosphere, 2023)

Genomic insights into the metabolic potential of a novel lignin-degrading and polyhydroxyalkanoates producing bacterium Pseudomonas sp. Hu109A - Muhammad Zohaib Nawaz; Huarong Shang; Jianzhong Sun; Alei Geng; Sameh S. Ali; Daochen Zhu (Chemosphere, 2023)

Cow bone-derived biochar enhances microbial biomass and alters bacterial community composition and diversity in a smelter contaminated soil - Muhammad Azeem; Parimala Gnana Soundari Arockiam Jeyasundar; Amjad Ali; Luqman Riaz; Khalid S. Khan; Qaiser Hussain; Hafiz A. Kareem; Fakhar Abbas; Abdul Latif; Ali Majrashi; Esmat F. Ali; Ronghua Li; et al. (Environmental Research, 2023)

Urban Heat Island vulnerability mapping using advanced GIS data and tools - Paras Sidiqui; Phillip B Roös; Murray Herron; David S Jones; Emma Duncan; Ali Jalali; Zaheer Allam; Bryan J Roberts; Alexander Schmidt; Muhammad Atiq Ur Rehman Tariq; Ashfaq Ahmed Shah; Nasir Abbas Khan; et al. (Journal of Earth System Science, 2022)

Evaluating the thermal-cooling induced effects on the Ambela granite properties (from Pakistan) using experimental and image processing techniques - Naseer Muhammad Khan; Liqiang Ma; Kewang Cao; Sajjad Hussain; Asghar Ali; Wei Liu; Saad S. Alarifi; Kausar Sultan shah; Sajid Khan; Yang Xiaoxu; Yujun Xu (Bulletin of Engineering Geology and the Environment, 2022)

Correction to: Role of casting and curing conditions on the strength and drying shrinkage of greener concrete - Muhammad Nasir; Adeyemi Adesina; Mohammed Ibrahim; Muhammad Umar Khan; Omar S. Baghabra Al‑Amoudi; Syed Imran Ali; Mohammed Maslehuddin; Khalid Saqer Alotaibi (Environmental Science and Pollution Research, 2022)

Role of casting and curing conditions on the strength and drying shrinkage of greener concrete - Muhammad Nasir; Adeyemi Adesina; Mohammed Ibrahim; Muhammad Umar Khan; Omar S. Baghabra Al-Amoudi; Syed Imran Ali; Mohammed Maslehuddin; Khalid Saqer Alotaibi (Environmental Science and Pollution Research, 2022)

Impact of Climate Change on Dryland Agricultural Systems: A Review of Current Status, Potentials, and Further Work Need - Mukhtar Ahmed; Rifat Hayat; Munir Ahmad; Mahmood ul-Hassan; Ahmed M. S. Kheir; Fayyaz ul-Hassan; Muhammad Habib ur-Rehman; Farid Asif Shaheen; Muhammad Ali Raza; Shakeel Ahmad (International Journal of Plant Production, 2022)

Modelling Climate Uncertainty and Adaptations for Soybean-Based Cropping System - Maryam Ejaz; Ghulam Abbas; Zartash Fatima; Pakeeza Iqbal; Muhammad Ali Raza; Ahmed M. S. Kheir; Mukhtar Ahmed; Khair Muhammad Kakar; Shakeel Ahmad (International Journal of Plant Production, 2022)

Comprehensive review on naringenin and naringin polyphenols as a potent anticancer agent - Abdur Rauf; Mohammad Ali Shariati; Muhammad Imran; Kashif Bashir; Shahid Ali Khan; Saikat Mitra; Talha Bin Emran; Kamala Badalova; Md. Sahab Uddin; Mohammad S. Mubarak; Abdullah S. M. Aljohani; Fahad A. Alhumaydhi; et al. (Environmental Science and Pollution Research, 2022)

Chromium (VI)-Induced Leaf-Based Differential Physiological, Metabolic and Microstructural Changes in Two Transgenic Cotton Cultivars (J208, Z905) and Their Hybrid Line (ZD14) - M. K. Daud; Shafaqat Ali; M. T. Variath; Mumtaz Khan; Muhammad Jamil; Maqsood Ahmad; S. J. Zhu (Journal of Plant Growth Regulation, 2022)

New approach in SARS-CoV-2 surveillance using biosensor technology: a review - Dina M. El-Sherif; Mohamed Abouzid; Mohamed S. Gaballah; Alhassan Ali Ahmed; Muhammad Adeel; Sheta M. Sheta (Environmental Science and Pollution Research, 2022)

In vitro α-glycosidase and urease enzyme inhibition profile of some selected medicinal plants of Pakistan - Abdur Rauf; Saud Bawazeer; Muhammad Naseer; Fahad A. Alhumaydhi; Abdullah S. M. Aljohani; Aamir Habib; Raheem Khan; Urooj Jehan; Muhammad Nasimullah Qureshi; Majid Khan; Umar Farooq; Amirzhan Kassenov; et al. (Natural Product Research, 2021)

Subtractive Proteomics and Immuno-informatics Approaches for Multi-peptide Vaccine Prediction Against Klebsiella oxytoca and Validation Through In Silico Expression - Qudsia Yousafi; Humaira Amin; Shabana Bibi; Rafea Rafi; Muhammad S. Khan; Hamza Ali; Ashir Masroor (International Journal of Peptide Research and Therapeutics, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Senegalin, a new phenylpropanoid and other secondary metabolites from the stem bark of Ekebergia senegalensis A. Juss. (Meliaceae) - Guy Paulin M. Kemayou; Gervais M. Happi; Yvan Anderson T. Ngandjui; Jean Claude Tchouankeu; Norbert Sewald; Muhammad S. Ali; Simeon F. Kouam (Natural Product Research, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Production of a broad spectrum streptothricin like antibiotic from halotolerant Streptomyces fimbriatus isolate G1 associated with marine sediments - Neelma Ashraf; Andreas Bechthold; Munir A. Anwar; Muhammad A. Ghauri; Muhammad S. Anjum; Ali N. Khan; Kalsoom Akhtar; Shazia Khaliq (Folia Microbiologica, 2021)

Physiological homeostasis for ecological success of Typha (Typha domingensis Pers.) populations in saline soils - Noreen Akhter; Muhammad Aqeel; Muhammad Muslim Shahnaz; Ghalia S. H. Alnusairi; Suliman Mohammed Alghanem; Abida Kousar; Mohamed Hashem; Hina Kanwal; Saad Alamri; Aisha Ilyas; Omar Mahmoud Al-zoubi; Ali Noman (Physiology and Molecular Biology of Plants, 2021)

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

Genetic architecture of wild soybean (Glycine soja Sieb. and Zucc.) populations originating from different East Asian regions - Muhammad Amjad Nawaz; Xiao Lin; Ting-Fung Chan; Hon-Ming Lam; Faheem Shehzad Baloch; Muhammad Amjad Ali; Kirill S. Golokhvast; Seung Hwan Yang; Gyuhwa Chung (Genetic Resources and Crop Evolution, 2021)

Pomegranate as a source of bioactive constituents: a review on their characterization, properties and applications - Maryam Pirzadeh; Nicola Caporaso; Abdur Rauf; Mohammad Ali Shariati; Zhanibek Yessimbekov; Muhammad Usman Khan; Muhammad Imran; Mohammad S. Mubarak (Critical Reviews in Food Science and Nutrition, 2021)

Identification of genetic variation for salt tolerance in Brassica napus using genome-wide association mapping - Ghulam Mustafa Wassan; Hira Khanzada; Qinghong Zhou; Annaliese S. Mason; Ayaz Ali Keerio; Saba Khanzada; Abdul Malik Solangi; Muhammad Faheem; Donghui Fu; Haohua He (Molecular Genetics and Genomics, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Biochar impact on microbial population and elemental composition of red soil - Zabih Ullah; Shafaqat Ali; Niaz Muhammad; Naeem Khan; Muhammad Rizwan; Muhammad Daud Khan; Niamat Khan; Baharullah Khattak; Haifa Abdulaziz S. Alhaithloul; Mona H. Soliman; Hamid Ullah; Dilnaz Begum; et al. (Arabian Journal of Geosciences, 2020)

Towards a Web GIS-based approach for mapping a dengue outbreak - Muhammad A. Butt; A. Khalid; A. Ali; S. A. Mahmood; J. Sami; J. Qureshi; K. Waheed; A. Khalid (Applied Geomatics, 2020)

Cytogenotoxicological Effects of the Methanolic Extract of Dysophylla auricularia - Muhammad Torequl Islam; Eunus S. Ali; Shaikh Jamal Uddin; Swati Tripathi; Ana Amélia de Carvalho Melo-Cavalcante; Siddhartha Kumar Mishra (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Bambara groundnut: an exemplar underutilised legume for resilience under climate change - Sean Mayes; Wai Kuan Ho; Hui Hui Chai; Xiuqing Gao; Aloyce C. Kundy; Kumbirai I. Mateva; Muhammad Zahrulakmal; Mohd Khairul Izwan Mohd Hahiree; Presidor Kendabie; Luis C. S. Licea; Festo Massawe; Tafadzwanashe Mabhaudhi; et al. (Planta, 2019)

Synthesis of 4-formyl pyridinium propylthioacetate stabilized silver nanoparticles and their application in chemosensing of 6-aminopenicillanic acid (APA) - A. Anwar; M. R. Shah; S. P. Muhammad; K. Ali; N. A. Khan (International Journal of Environmental Science and Technology, 2019)

Effects of road proximity on heavy metal concentrations in soils and common roadside plants in Southern California - Noreen Khalid; Mumtaz Hussain; Hillary S. Young; Benjamin Boyce; Muhammad Aqeel; Ali Noman (Environmental Science and Pollution Research, 2018)

Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters - Rima W. Jabado; Peter M. Kyne; Riley A. Pollom; David A. Ebert; Colin A. Simpfendorfer; Gina M. Ralph; Shaikha S. Al Dhaheri; K. V. Akhilesh; Khadeeja Ali; Mohamud Hassan Ali; Tariq M. S. Al Mamari; K. K. Bineesh; et al. (Fish and Fisheries, 2018)
The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.

Identification, Characterization and Expression Profiles of Dof Transcription Factors in Pineapple (Ananas comosus L) - Syed Muhammad Azam; Yanhui Liu; Zia Ur Rahman; Hina Ali; Cheng Yan; Lulu Wang; S. V. G. N. Priyadarshani; Binyan Hu; Xinyu Huang; Junjie Xiong; Yuan Qin (Tropical Plant Biology, 2018)

Bt Proteins Have No Detrimental Effects on Larvae of the Green Lacewing, Chrysopa pallens (Rambur) (Neuroptera: Chrysopidae) - I Ali; S Zhang; M S Muhammad; M Iqbal; J-J J-J Cui (Neotropical Entomology, 2018)

Expression Profiles of Wuschel-Related Homeobox Gene Family in Pineapple (Ananas comosus L) - Zia ur Rahman; Syed Muhammad Azam; Yanhui Liu; Cheng Yan; Hina Ali; Lihua Zhao; Piaojuan Chen; Li Yi; S. V. G. N. Priyadarshani; Qin Yuan (Tropical Plant Biology, 2017)

Leaf-based physiological, metabolic, and ultrastructural changes in cultivated cotton cultivars under cadmium stress mediated by glutathione - M. K. Daud; Lei Mei; Azizullah Azizullah; Muhammad Dawood; Imran Ali; Qaisar Mahmood; Waheed Ullah; Muhammad Jamil; S. J. Zhu (Environmental Science and Pollution Research, 2016)

Remediation of arsenic-contaminated water using agricultural wastes as biosorbents - Muhammad Bilal Shakoor; Nabeel Khan Niazi; Irshad Bibi; Ghulam Murtaza; Anitha Kunhikrishnan; Balaji Seshadri; Muhammad Shahid; Shafaqat Ali; Nanthi S. Bolan; Yong Sik Ok; Muhammad Abid; Fawad Ali (Critical Reviews in Environmental Science and Technology, 2016)

Comparative Assessment of Synthetic-derived and Conventional Bread Wheat Advanced Lines Under Osmotic Stress and Implications for Molecular Analysis - Ahmad Ali; Muhammad Arshad; S. M. Saqlan Naqvi; Awais Rasheed; Hassan Sher; Alvina Gul Kazi; Abdul Mujeeb-Kazi (Plant Molecular Biology Reporter, 2015)

Seleniferous soils as a source for production of selenium-enriched foods and potential of bacteria to enhance plant selenium uptake - Muhammad Yasin; Ali F. El Mehdawi; Courtney E. Jahn; Aneela Anwar; Marie F. S. Turner; Muhammad Faisal; Elizabeth A. H. Pilon-Smits (Plant and Soil, 2015)

Exploitation of synthetic-derived wheats through osmotic stress responses for drought tolerance improvement - Ahmad Ali; Muhammad Arshad; S. M. Saqlan Naqvi; Manzoor Ahmad; Hassan Sher; Sammer Fatima; Alvina Gul Kazi; Awais Rasheed; Abdul Mujeeb-Kazi (Acta Physiologiae Plantarum, 2014)

Changes in extreme temperature and precipitation in the Arab region: long‐term trends and variability related to ENSO and NAO - M. G. Donat; T. C. Peterson; M. Brunet; A. D. King; M. Almazroui; R. K. Kolli; Djamel Boucherf; Anwar Yousuf Al‐Mulla; Abdourahman Youssouf Nour; Ahmed Attia Aly; Tamer Ali Ali Nada; Muhammad M. Semawi; et al. (International Journal of Climatology, 2014)
A workshop was held in Casablanca, Morocco, in March 2012, to enhance knowledge of climate extremes and their changes in the Arab region. This workshop initiated intensive data compilation activities of daily observational weather station data from the Arab region. After conducting careful control processes to ensure the quality and homogeneity of the data, climate indices for extreme temperatures and precipitation were calculated. This study examines the temporal changes in climate extremes in the Arab region with regard to long‐term trends and natural variability related to ENSO and NAO . We find consistent warming trends since the middle of the 20th Century across the region. This is evident in the increased frequencies of warm days and warm nights, higher extreme temperature values, fewer cold days and cold nights and shorter cold spell durations. The warming trends seem to be particularly strong since the early 1970s. Changes in precipitation are generally less consistent and characterised by a higher spatial and temporal variability; the trends are generally less significant. However, in the western part of the Arab region, there is a tendency towards wetter conditions. In contrast, in the eastern part, there are more drying trends, although, these are of low significance. We also find some relationships between climate extremes in the Arab region and certain prominent modes of variability, in particular El Niño‐Southern Oscillation ( ENSO ) and North Atlantic Oscillation ( NAO ). The relationships of the climate extremes with NAO are stronger, in general, than those with ENSO , and are particularly strong in the western part of the Arab region (closer to the Atlantic Ocean). The relationships with ENSO are found to be more significant towards the eastern part of the area of study. © 2013 Royal Meteorological Society

Inferring the contribution of sexual reproduction, migration and off‐season survival to the temporal maintenance of microbial populations: a case study on the wheat fungal pathogen P uccinia striiformis f.sp. tritici - Sajid Ali; Pierre Gladieux; Hidayatur Rahman; Muhammad S. Saqib; Muhammad Fiaz; Habib Ahmad; Marc Leconte; Angélique Gautier; Annemarie F. Justesen; Mogens S. Hovmøller; Jérôme Enjalbert; Claude de Vallavieille‐Pope (Molecular Ecology, 2014)
Understanding the mode of temporal maintenance of plant pathogens is an important domain of microbial ecology research. Due to the inconspicuous nature of microbes, their temporal maintenance cannot be studied directly through tracking individuals and their progeny. Here, we suggest a series of population genetic analyses on molecular marker variation in temporally spaced samples to infer about the relative contribution of sexual reproduction, off‐season survival and migration to the temporal maintenance of pathogen populations. We used the proposed approach to investigate the temporal maintenance of wheat yellow rust pathogen, P uccinia striiformis f.sp. tritici ( PST ), in the H imalayan region of P akistan. Multilocus microsatellite genotyping of PST isolates revealed high genotypic diversity and recombinant population structure across all locations, confirming the existence of sexual reproduction in this region. The genotypes were assigned to four genetic groups, revealing a clear differentiation between zones with and without B erberis spp., the alternate host of PST , with an additional subdivision within the B erberis zone. The lack of any differentiation between samples across two sampling years, and the very infrequent resampling of multilocus genotypes over years at a given location was consistent with limited over‐year clonal survival, and a limited genetic drift. The off‐season oversummering population in the B erberis zone, likely to be maintained locally, served as a source of migrants contributing to the temporal maintenance in the non‐ B erberis zone. Our study hence demonstrated the contribution of both sexual recombination and off‐season oversummering survival to the temporal maintenance of the pathogen. These new insights into the population biology of PST highlight the general usefulness of the analytical approach proposed.

Seasonal variation in essential oil yield and composition from Thymus vulgaris L. during different growth stages in the south of Jordan - Mohammad S. Abu-Darwish; Muhammad H. Alu’datt; Abdel Rahman Al-Tawaha; Khalil Ereifej; Ali Almajwal; Nidal Odat; Wesam Al Khateeb (Natural Product Research, 2012)

Localization of a novel locus for alopecia with mental retardation syndrome to chromosome 3q26.33–q27.3 - Peter John; Ghazanfar Ali; Muhammad S. Chishti; Syed Muhammad S. Naqvi; Suzanne M. Leal; Wasim Ahmad (Human Genetics, 2006)

Response of three wheat genotypes grown under saline medium to low/high potassium levels - M. U. Shirazi; B. Khanzada; Muhammad Ali; Ejaz ul Islam; S. M. Mujtaba; R Ansari; S. M. Alam; M. A. Khan; Mukhtiar Ali (Acta Physiologiae Plantarum, 2002)

A Preliminary Comparison of Plasma Fibrinogen Concentrations, Leukocyte Numbers and Erythrocyte Sedimentation Rate as Non-Specific Indicators of Inflammatory Conditions in Buffalo (Bubalis Bubalis) - M. Zargham Khan; G. Muhammad; A. Umar; S. Ali Khan (Veterinary Research Communications, 1997)